2006
DOI: 10.1111/j.1538-7836.2006.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet nitric oxide synthase is activated by tyrosine dephosphorylation: possible role for SHP‐1 phosphatase

Abstract: Summary. Background: Endothelial nitric oxide synthase (eNOS) activity in endothelial cells is regulated by posttranslational phosphorylation of critical serine, threonine and tyrosine residues in response to a variety of stimuli. However, the post-translational regulation of eNOS in platelets is poorly defined. Objectives: We investigated the role of tyrosine phosphorylation in the regulation of platelet eNOS activity. Methods: Tyrosine phosphorylation of eNOS and interaction with the tyrosine phosphatase SHP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(45 reference statements)
2
14
0
Order By: Relevance
“…This is of special interest especially in the light of a previous study where platelets isolated from “motheaten viable mice”, which have a defect in the SHP-1 gene, were hyporesponsive to GPVI stimulation suggesting a physiological role for SHP-1 in lowering the threshold for activation by GPVI [27]. In addition, a role for SHP-1 in the regulation of platelet eNOS has been reported [37]. To elucidate whether the observed prothrombotic effects in vivo could be due to direct effects of SHP-1 inhibition by sodium stibogluconate in platelets we performed in vitro (human PRP) and ex vivo (mouse blood) aggregation studies.…”
Section: Discussionmentioning
confidence: 99%
“…This is of special interest especially in the light of a previous study where platelets isolated from “motheaten viable mice”, which have a defect in the SHP-1 gene, were hyporesponsive to GPVI stimulation suggesting a physiological role for SHP-1 in lowering the threshold for activation by GPVI [27]. In addition, a role for SHP-1 in the regulation of platelet eNOS has been reported [37]. To elucidate whether the observed prothrombotic effects in vivo could be due to direct effects of SHP-1 inhibition by sodium stibogluconate in platelets we performed in vitro (human PRP) and ex vivo (mouse blood) aggregation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of platelets with sodium orthovanadate, a tyrosine phosphatase inhibitor, increased tyrosine phosphorylation of NOS, resulting in a concomitant decrease in basal enzyme activity and blunting of thrombin‐induced cGMP formation [61]. Consistent with this, dephosphorylation of NOS from thrombin‐stimulated platelets increased enzyme activity, suggesting that cellular phosphatases play a role in NOS activation [62]. Furthermore, we found that platelet eNOS formed a complex with SHP‐1 phosphatase, and that SHP‐1 regulated NO synthesis in response to thrombin [62].…”
Section: Platelet Nitric Oxide Synthasementioning
confidence: 95%
“…Initial studies suggested that phosphorylation of unknown serine/threonine and tyrosine residues controls the activity of NOS in collagen‐stimulated platelets [67]. Using phosphospecific NOS antibodies, only phosphorylation at ser 1177 has been demonstrated in platelet NOS, but only in response to insulin [48] and adenosine [50] and not platelet agonists [61,62]. Insulin induces phosphorylation of platelet NOS on ser 1177 through activation of PI3kinase and AMP activated protein kinase (AMPK), and this was associated with increased cGMP levels [48].…”
Section: Platelet Nitric Oxide Synthasementioning
confidence: 99%
“…Platelet stimulation by thrombin further increases SHP-1 association with eNOS. Association of SHP-1 with eNOS was confirmed in both resting and thrombin-activated platelets, but it was not 2204 HENEBERG detected in the endothelial cells (68). Platelet treatment with 0.1-1.0 mM sodium orthovanadate was shown to increase tyrosine phosphorylation of eNOS, leading to the decrease of basal eNOS activity and the blunting of thrombin-induced guanosine 3¢,5¢-monophosphate (cGMP) formation; the vanadate-induced changes were abolished when the platelets were preincubated with the Src kinase inhibitor PP2, but not by the PKC inhibitor Ro-31-8220 or PI3K inhibitor wortmannin (61).…”
Section: Multiple Roles Of Shp-1 In No Productionmentioning
confidence: 91%